Pain management for pediatric tonsillectomy: An integrative review through the perioperative and home experience. Issue 1 (21st August 2013) - Howard, Dekeisha; Davis, Katherine Finn; Phillips, Eileen; Ryan, Eileen; Scalford, Deborah; Flynn‐Roth, Regina; Ely, Elizabeth
Abstract Purpose This integrative review aims to increase our understanding of current pain management care practices for children undergoing tonsillectomy. Conclusions Synthesis of the literature resulted in four main opportunities for care providers to manage pain: preoperative education and preparation, intraoperative surgical interventions, and postoperative pharmacologic and nonpharmacologic interventions in the post anesthesia care unit and home settings. Practice Implications Nurses have many opportunities to understand pain management practices and intervene to minimize pain experienced in pediatric outpatients undergoing tonsillectomy.